The Social Support Buffering Effect in the Relationship Between Perceived Stress and Alcohol Use Among Brazilian Women. - de Souza, Jacqueline; de Almeida, Letícia Yamawaka; de Oliveira, Jordana Luiza Gouvêa; Miasso, Adriana Inocenti; Pillon, Sandra Cristina; Moll, Marciana Fernandes (Community Mental Health Journal, 2019)
This cross-sectional study interviewed Brazilian women regularly attending primary care to investigate whether the relationship between social support and alcohol use is direct or is mediated by stress, in order to support the development of recommendations related to health prevention and mental health promotion actions. The results suggest that social support affects the outcome alcohol use in the women studied by buffering the effect of stress. Based on these results, recommendations are made for amplifying the social support network that prevents stress-induced alcohol use.